The Effect of Institutional Ownership, Company Size, Leverage, and Profitability on Firm Value - Daud Muharam; Lucky Nugroho (Baca Dulu Publisher, 2025)
This study aims to analyze the effect of Institutional Ownership, Company Size, Leverage, and Profitability on Firm Value. The population in this study are companies listed on the IDX (Indonesia Stock Exchange) in 2018-2022. The sample of this study amounted to 19 companies with 5 years of observation, so the total sample was 95 sample data. The sampling method was carried out by using purposive sampling method. The data analysis method used in this research is multiple linear analysis. The results of this study indicate that Company Size and Leverage have an influence on firm value in companies in the Non-Cylical Consumer Sector of the processed food and beverage sub-industry listed on the Indonesia Stock Exchange (IDX) during the period 2018 to 2022.